Comparative Effects of Two High-Intensity Intermittent Training Programs on Sub-Elite Male Basketball Referees' Fitness Levels - David Suárez-Iglesias; Alejandro Rodríguez-Fernández; Alejandro Vaquera; José Gerardo Villa-Vicente; Jose A. Rodríguez-Marroyo (MDPI AG, 2024)
This study aimed to compare the effects of an 8-week short-term training program, comprising repeated sprints or running-based high-intensity intermittent training (HIIT), on the aerobic fitness and repeated sprint ability (RSA) performance of sub-elite basketball referees. Twenty male referees participated in supervised training sessions twice a week. They were randomly assigned to either the RSA-based group (RSAG) or the running-based HIIT group (HIITG). The RSAG conducted 3-4 sets of 8 × 20-m all-out sprints, while the HIITG performed 2-3 sets of 6 × 20-s runs at 90% of their maximal velocity achieved in the 30-15 intermittent fitness test (30-15IFT). Referees underwent a graded exercise test on a treadmill, the 30-15IFT, and an RSA test before and after the training program. Both groups showed significant improvement (~3%) in the fastest (22.6 ± 1.4 vs. 23.4 ± 1.7 and 22.0 ±1.9 vs. 22.4 ± 1.7 km·h−1 in RSAG and HIITG, respectively) and mean (21.5 ± 1.2 vs. 22.4 ± 1.4 and 21.3 ± 1.8 vs. 21.7 ± 1.6 km·h−1 in RSAG and HIITG, respectively) sprint velocity of the RSA test (p < 0.05). Moreover, positive changes (p < 0.05) were observed in the 30-15IFT maximal velocity (18.6 ± 1.1 vs. 19.3 ± 1.0 and 19.4 ± 0.9 vs. 20.5 ± 0.9 km·h−1 in RSAG and HIITG, respectively). In conclusion, an 8-week training intervention using either RSA or running-based HIIT led to similar improvements in referees' RSA performance and specific aerobic fitness measures. These findings could assist in devising tailored training programs for basketball referees.